CUSTOMER PERCEPTION OF ONLINE BANKING IN INDIA: PUNJAB - Singh, Zorawar (2012)
The emergence and adoption of information technology has turned the world into a global village. India being an emerging market, it cannot afford to ignore the benefits of information technology especially in the banking sector. The financial services sector realized the importance of the internet as a way of connecting and interacting with clients. From the customers point of view internet banking is a boon. Registered online customers can perform common banking transactions such as paying bills; writing checks, transferring funds, printing statements and inquiring about account balances. But what is most intriguing is that with all the benefits of online banking why has the Indian consumer not adopted internet banking and felt its potential. This piece of work studies the customer perception of online banking in India, Punjab. Goyal and Joshi (2011b) say that a significant element of organizational relationship is customer perception, which helps to achieve the expected customer’s expectations and satisfaction level. The challenges experienced by Indian banks in achieving quality service deliveries were associated with their failure to compensate, support and train their users on their online banking services. In particular, this was realized to impede the adoption rate due to mismatches between promises and outcomes.